Effects of tetrandrine on free intracellular Ca2+ in isolated rat brain cells - Zeng Wei-Zhong; Liu Tian-Pei (Acta Pharmacologica Sinica; Vol 14, No 5 (September 1993): Acta Pharmacologica Sinica, 2016)
Using Ca(2+)-sensitive fluorescent indicator, Fura-2/AM, intracellular free Ca2+ ([Ca2+]i) was measured. Resting [Ca2+]i was 221 +/- 18 nmol.L-1 in the presence of Ca2+ 1.3 mmol.L-1 in Hank's solution. Tetrandrine (Tet) 30 mumol.L-1 had no effect on the resting [Ca2+]i when the extracellular Ca2+ were 0-2 mmol.L-1. In the presence of extracellular Ca2+ 1.3 mmol.L-1, Tet (1-100 mumol.L-1) concentration-dependently inhibited the high extracellular K(+)-induced [Ca2+]i elevation, with an IC50 value of 8.2 mumol.L-1 (95% confidence limits: 1.9-32.9 mumol.L-1). Low concentrations of Tet (1-10 mumol.L-1) did not alter the norepinephrine-induced [Ca2+]i elevation. Tet 30 mumol.L-1 depressed norepinephrine 10 mumol.L-1 induced [Ca2+]i elevation by 42%. The results suggested that Tet inhibited the Ca2+ influx through voltage-dependent ionic channels and, at high concentrations, through receptor-operated ionic channels in the brain cells.